Reassessing lidocaine as an electroporation sensitizer in vitro - Anja Blažič; Rok Šmerc; Tamara Polajžer; Damijan Miklavčič; Lea Rems (Scientific Reports)
Abstract High-intensity pulsed electric fields induce transient increase in membrane permeability, a phenomenon known as electroporation, with broad applications in medicine, including electrochemotherapy (ECT), gene electrotransfer and tissue ablation. As electroporation technologies become increasingly established in clinical practice, understanding how commonly used pharmacological agents influence treatment outcomes is gaining importance. Lidocaine, a widely used local anesthetic and ion channel modulator, has recently been investigated as a potential sensitizer to enhance the efficacy of electroporation. Here, we examined the effects of lidocaine on membrane permeabilization and cell viability using standard 8 × 100 µs ECT pulses across four cell lines: melanoma B16-F1, myoblast C2C12, CHO-K1 cells with low ion channel expression, and NS-HEK cells with stable Nav1.5 expression. We show that 10 mM lidocaine has only modest effects on electroporation outcomes, while 35 mM considerably lowers the electric field threshold for irreversible electroporation by 25–40% in melanoma cells. However, concentrations of even 10 mM exceed those reported in tissues following local administration of lidocaine. This questions the clinical relevance of lidocaine’s sensitization effect and warrants further investigation. Our study also highlights the importance of evaluating drug–electroporation interactions under rigorously controlled experimental conditions to ensure meaningful translation into clinical applications.